evaluate using identity (x-2/3y)^3
Answers
Answered by
0
Answer:
( a - b)³ = a³ - b³ -3ab (a-b)
Then,
(x- \frac{2}{3y})^{3}= x^{3}- (\frac{2}{3y})^{3}- \frac{2x}{y}(x- \frac{2}{3y})(x−
3y
2
)
3
=x
3
−(
3y
2
)
3
−
y
2x
(x−
3y
2
)
⇒ x^{3}- \frac{8}{27y^{3}} - \frac{2x^{2}}{y}+ \frac{2x}{3y^{2}}x
3
−
27y
3
8
−
y
2x
2
+
3y
2
2x
Answered by
0
Answer:
We know that,
(a-b)³ = a³- b³ - 3ab(a-b)
[(x-2)/3y]³
=(x-2)³/(3y)³
= x³ - 8 - 6x(x-2) / 27y³
Step-by-step explanation:
pls mark on brainlist
Similar questions